Hubungan Interaksi Sosial Dan Aktivitas Fisik Dengan Fungsi Kognitif Pada Lansia Di Wilayah RW 05 Kelurahan Cilangkap Kecamatan Tapos Kota Depok Tahun 2023 - Alya Fauziah; Saiful Gunardi; Emi Yuliza (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
The decline in cognitive function can be influenced by various factors, both individual and environmental. Individual factors include age, gender, level of education, genetic factors, and medical history. Meanwhile, environmental factors include social engagement and activities, both physical and cognitive activities. This research aims to investigate the Relationship between Social Interaction and Physical Activity with Cognitive Function in the Elderly Population in Neighborhood 05 of Cilangkap Subdistrict, Tapos District, Depok City. The method used in this research utilizes a quantitative approach with a cross-sectional design, involving a sample of 55 respondents. The research results showed that the majority of respondents had good social interaction, totaling 32 respondents out of the total respondents. Of these, 23 (71.0%) respondents had a normal cognitive function, while 9 (28.1%) respondents experienced moderate cognitive impairment. Additionally, the majority of respondents with good physical activity and normal cognitive function amounted to 22 respondents (75.9%), while respondents with good physical activity and moderate cognitive impairment numbered 7 respondents (24.1%). In conclusion, the majority of respondents with good social interaction and good physical activity tended to have normal cognitive function.